Development and design of automated hospital bed with incremental panels for bedsore prevention - Bandala, Argel A. (Animo Repository, 2015)
The common causes of Bedsores are constant pressure and moisture build-up. To prevent the development of these causes, the researchers have decided to modify the typical hospital bed into an electronically automated prototype. The prototype was built with 50 incremental panels that has the capability to move the patient on the by the combination of the Chain and Sprocket Method and the Lead Screw. These incremental panels were implemented with Temperature Sensors to monitor the ambient temperature on the bed surface and IR Proximity sensors to detect the location of the patient in the prototype. The data gathered by these sensors are processed through the use of a microcontroller. The microcontroller will then relay the processed data to the stepper motor driver which will manipulate the stepper motors to cause movement to the incremental panels. © 2014 IEEE.